Crenças e vivências da infidelidade na contemporaneidade - Santos, Lais Rocha (2018)
The general aim of this paper is to analyze how Adultery has been felt, researched and lived in the contemporaneity. To do so, 3 studies were held. The study number 1 identified how this behavior has been investigated across the country by the national scientific communities by the use of a integrative review of literature. It was clear this subject is poorly investigated nationally, scientific journals report mostly about causes, repercussions and phenomena related to questions of the infidelity in the contemporaneity. The study number 2 analyzed quantitatively how the adultery has been realized and felt in the modern relationships; an online sociodemographic survey, scales and inventories were applied. The study also reported about proximity and distance between genders through infidelity experiences from main social constructs related to sexual satisfaction of married people. Important subjects linked to the adultery were reported, mainly the ones related to conjugality, sexuality, beliefs and thoughts about infidelity, marriage and the modernity itself which creates the possibility of having sex easily. The study number 3 reported about subjects related to adultery and the involved partners in such situation, plus the way which the infidelity is seen and felt in their relationships. Six people were interviewed and from their narratives it is possible to verify that setting up causes and predictors is a very dangerous path, which can reduce the multiplicity of involved factors. Beyond that it is relevant to discuss the satisfaction in the social environment and the way that relationships are made nowadays in the contemporaneity and its multiplicity of information, stimuli and new ways of relationships through the internet.